If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x) + 5 = (5x) + -12 Reorder the terms: 5 + (6x) = (5x) + -12 Reorder the terms: 5 + (6x) = -12 + (5x) Solving 5 + (6x) = -12 + (5x) Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(-5x)' to each side of the equation. 5 + (6x) + (-5x) = -12 + (5x) + (-5x) Combine like terms: (6x) + (-5x) = 1x 5 + 1x = -12 + (5x) + (-5x) Combine like terms: (5x) + (-5x) = 0 5 + 1x = -12 + 0 5 + 1x = -12 Add '-5' to each side of the equation. 5 + -5 + 1x = -12 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = -12 + -5 1x = -12 + -5 Combine like terms: -12 + -5 = -17 1x = -17 Divide each side by '1'. x = -17 Simplifying x = -17
| 45+24h=405 | | x^2+2x-7=-7x+3 | | 2x-8+2x-7=15 | | -0.6+(-0.3)= | | -4+(v-2)=-4(v-8)-8v | | 3x-5x+7=-21 | | 4(x-3)-1=3x | | 4n+2=6n+8 | | 7=-11+3(y+5) | | 3y=-5x+6 | | m^2+mn-6n^2=0 | | 3x+4xy-(4x-xy+xyz)= | | 19=-2p+23 | | 0=14x+28 | | 6(4-w)=2w | | 5x-3=3(x+6) | | 3/2=18÷x | | 6a-5b=1 | | X^2+3x-12+-6=0 | | 3x+4-9-4x=12 | | v=4/3*3.14*(21)3 | | 4x=2(48-4) | | h/6-1= | | x(4x-6)=(4x+7)(x-5) | | 5X1/14 | | 2x+x-24=90 | | X-1=4x-22 | | 4x=2(48-3) | | 15x-3x+2(x+4)=48 | | z^2+3z=-1 | | 13-4t+5t=-5-2 | | 11/4y-3/12y=10 |